MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH MELALUI METODE PROYEK PADA KELOMPOK B - Romlah, Romlah; Santana, Fifiet Dwi Tresna (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2021)
This research aims to improve the ability to solve problems through project methods. The method chosen is classroom action research. The research is located in the city of Cianjur. Data collection techniques were carried out through observation and documentation techniques for 17 children. Data analysis techniques were obtained from field data, by using qualitative data analysis techniques.  Focused on the data collected, namely from research instruments, interview guides, observation, and documentation. Data analysis is performed after the data obtained from the sample through the instrument chosen and will be used to answer the research problem. The results showed that there was an increase in the ability to solve children's problems with learning using the project method. The initial pre-action is in the lack category. In line with the implementation of the project method, children experienced an increase in cycle II of 57.14% with a very well developed category (BSB). Indicators of increasing skills are at the level of children who can make observations by using the senses properly. This also happens to the indicator of the ability to gather information and communicate. However, of course, the child still needs motivation and stimulus from his teacher, so that the child can be optimal in developing and enhancing their abilities and be brave in asking questions and being able to answer questions given by the teacher.Penelitian ini bertujuan untuk meningkatkan kemampuan memecahkan masalah melalui metode proyek. Metode yang dipilih yaitu penelitian tindakan kelas. Penelitian berlokasi di kota Cianjur. Teknik pengumpulan data dilakukan melalui teknik obervasi dan dokumentasi terhadap 17 anak. Teknik analisis data ini diperoleh dari data dilapangan, dengan menggunakan teknik analisis data kualitatif. Difokuskan kepada data yang terkumpul yaitu dari instrument penelitian, pedoman wawancara, observasi dan dokumentasi. Hasil penelitian terlihat bahwa adanya peningkatan kemampuan memecahkan masalah anak dengan pembelajaran menggunakan metode proyek. Awal pra tindakan berada pada kategori kurang. Sejalan dengan diterapkannya metode proyek, anak mengalami peningkatan pada siklus II yaitu sebesar 57.14% dengan kategori berkembang sangat baik (BSB). Indikator meningkatnya keterampilan tersebut yaitu pada tingkat anak sudah mampu melakukan pengamatan dengan menggunakan inderanya dengan baik. Hal ini terjadi pula pada indikator kemampuan mengumpulkan informasi dan mengkomunikasikan. Namun hal tersebut tentu saja anak masih membutuhkan motivasi dan stimulus dari gurunya, agar anak bisa optimal dalam mengembangkan dan meningkatkan kemampuannya serta berani dalam bertanya  dan mampu menjawab pertanyaan yang diberikan oleh guru.